The impact of an endometriosis diagnosis on employment status and earnings among women in England - Ward, Isobel; Bunk, Hannah; Campbell, Emma; Sharp, Gemma; Ayoubkhani, Daniel; Nafilyan, Vahé (International Journal of Population Data Science, 2025)
Objectives Endometriosis has physical, psychological, social, and economic impacts; however, no previous population-level research has quantified the labour market impacts of this condition in England. We linked employee pay records to census data and endometriosis diagnoses to examine the impact of an endometriosis diagnosis on women's labour market participation and progression. Methods We used de-identified monthly employee pay records from HM Revenue and Customs (HMRC) linked to Hospital Episode Statistics (HES) and Census 2011. Our study population included 55,920 women who had a diagnosis of endometriosis in an NHS hospital between 2016 and 2022, were aged 25-to-54-years at time of diagnosis, and could be linked to HMRC and census data. We used fixed effects regression modelling to estimate the average changes in employee pay and employment status attributable to being diagnosed with endometriosis. Outcomes were estimated at different time periods after diagnosis, compared with the two years before diagnosis. Results Compared with the two-year period before being diagnosed with endometriosis, monthly pay initially dropped on average in the first three months post-diagnosis, then returned to pre-diagnosis levels from 4 to 12 months. Afterward, there was a statistically significant average decrease in monthly earnings among women from one to five years after diagnosis. Among women in paid work, monthly pay reached an average decrease of £56 (95%CI:£29-£83) per month in the four to five years post-diagnosis. This suggests that, following a diagnosis, women in work may be taking lower-paying jobs or working fewer hours. The probability of being a paid employee decreased by 2.7 percentage points in the four to five years post-diagnosis, compared with the two years before diagnosis. Conclusion Our findings show that following an endometriosis diagnosis, women earn less and are less likely to be in paid employment compared with the two years before diagnosis. These results highlight a clear need for a review of appropriate healthcare services and policies around endometriosis and the workplace.